Pengaruh Upah Minimum dan Angka Melek Huruf Terhadap Tingkat Pengangguran dan Kemiskinan di Provinsi Bali - Yoga, I Made Sedana; Putra, I Komang Trisna Eka; Utomo, Rochmad Bayu (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2022)
The significant increase in the number of poor and unemployed people in the Province of Bali over the past two years as part of the impact of the Covid-19 pandemic which hit the joints of the economy has become a new problem that deserves further handling. This research is focused on discussing the causes of poverty by focusing on the employment aspect which includes wages and unemployment, as well as the educational aspect which is represented by the literacy rate indicator. The research objectives in this study are: (1) to analyze the effect of minimum wages and literacy rates on unemployment in Bali Province; (2) to analyze the effect of minimum wages, literacy rates, and unemployment on poverty in Bali Province; and (3) to analyze the role of unemployment in mediating the effect of minimum wages and literacy rates on poverty in Bali Province. The approach used in this study is a quantitative approach. This study uses path analysis techniques in hypothesis testing. Secondary data were obtained from the Central Bureau of Statistics (BPS) of Bali Province, and this study combined time series data and cross sectional data or in the form of panel data. The data processing aids used were Microsoft Excel and Eviews version 10. The results showed that (1) the minimum wage and literacy rate had a positive but not significant effect on unemployment; (2) the minimum wage has a negative and insignificant effect on poverty, the literacy rate has a direct negative and significant effect on poverty, and unemployment has a direct positive and significant effect on poverty; and (3) unemployment does not mediate the effect of minimum wages and literacy rates on poverty in Bali Province.